Trajetórias e dinâmicas de mobilidade migrante no oeste paulista: sírios e libaneses em Bariri – décadas de 1900 a 1950 - Martinez, Miguel Brandão (Universidade Federal de São Carlos, 2024)
From the second half of the 19th century onwards, the state of São Paulo began to receive various nationalities of immigrants. Among the main nationalities that arrived in the state were those of European origin, especially Italians, Spaniards and Portuguese. From the 1870s onwards, immigrants from Asia began to arrive, especially Syrians and Lebanese, who, unlike the other nationalities, were not subsidized immigrants. They initially concentrated in the capital of São Paulo, beginning their professional careers as peddlers and later opening stores, especially in Rua 25 de Março. Over the years, they encouraged their fellow countrymen to come, and when they arrived, they received help from those who were already established and began their professional journey in the commercial sector. As the coffee plantations and railroads expanded into the western region, the Syrians and Lebanese took advantage of the booming economy of the newly formed cities and spread throughout the interior of the state. One of the cities that had the presence of these immigrants was Bariri, located just over 300 kilometers from the capital of São Paulo. This research sought to analyze the trajectory of the colony formed there and the dynamics of socio-economic mobility experienced by its members. Therefore, primary and secondary sources were analyzed, such as the records of the National Registry of Foreigners, historical periodicals, bibliographical productions about the municipality and interviews with the descendants of the pioneer immigrants. The data obtained made it possible to understand that the local colony became involved in the commercial sector, transforming it into an ethnic niche, which enabled the accumulation of financial capital used to re-establish families in the São Paulo municipality through a migratory network with certain villages. These factors contributed to a high degree of social cohesion among the inhabitants, enabling the founding of the Syria de Beneficencia Society and the construction of the St. George Antiochian Orthodox Church. It was also possible to identify that some pioneers directed their efforts towards the intellectual education of their children, especially in the liberal professions, which in the future enabled them to run for political office.
Trajectories and dynamics of migrant mobility in western São Paulo: syrians and lebanese in Bariri – 1900s to 1950s
Keywords: Migração; Sírios e libaneses; Oeste paulista; Sociologia histórica; Micro-história; Migration; Syrians and lebanese; Western São Paulo; Historical sociology; Microhistory; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS